Oral and transdermal administration of lipopolysaccharide safely enhances self-healing ability through the macrophage network - Soma, Gen-Ichiro; Oda, Masataka; Tjhin, Vindy Tjendana; Kohchi, Chie; Inagawa, Hiroyuki (Frontiers in Immunology, 2025)
Lipopolysaccharide (LPS), also known as an endotoxin, is derived from Gram-negative bacteria. The intravenous administration of LPS induces an inflammatory response and causes systemic inflammation, such as cytokine storm. Gram-negative bacteria that produce LPS are found in the environment and digestive tract. The mucous membrane, the primary barrier between the interior of the body and the external environment, is constantly exposed to LPS. Moreover, no toxicity is observed when administering LPS through the mucous membranes of the mouth or skin. The presence of LPS in the mucous membranes is necessary not only for maintaining health but also for inducing preventive and therapeutic effects against multiple diseases when administered orally or topically. LPS is an environmental substance that is useful when administered to mucous membranes. The general information emphasizes the role of LPS as an inflammatory substance that occurs when administered intravenously. Therefore, the valuable role of LPS is unknown. Thus, mucosal administration of LPS has received little attention, and the mechanism underlying the expression of its beneficial effects has not been fully elucidated. We proposed a comprehensive concept, the “macrophage network,” which proposes a regulatory system in which the mucosa receives environmental information, membrane-bound cytokines are expressed in phagocytes (macrophages), and these macrophages migrate distally to exert effects, such as anti-inflammatory and tissue repair effects, on distal tissues through cell-to-cell communication (juxtacrine signaling) with tissue macrophages. This macrophage network is effective not only for preventing and treating diseases but also for increasing the efficacy of pharmaceuticals. This review aims to investigate the preventive and therapeutic effects of oral and transdermal administration of LPS on various diseases and present an introduction to the concept of the macrophage network and the latest findings.